PERSPEKTIF JHON PAULO FREIRE DAN KI HADJAR DEWANTARA TERHADAP INTEGRASI INTELEKTUALITAS DAN MORALITAS PESERTA DIDIK DALAM MENYADARI KEMAJEMUKAN DI INDONESIA - Ahmad Dahri (Fakultas Tarbiyah, Universitas Ibrahimy, 2018)
The real purpose of education is humanizing human beings. The most prominent thing in humanity is diversity, plurality or multiculturality. Indonesia is a country consisting of a plural society. This should be realized by all individuals in this nusantara society. Providing awareness of the existence of mulitikulturalitas or pluralism can be pursued in the educational process. For the sake of this interest, then in the educational process there must be some kind of integralization effort between forming the intellect and morality of learners. The function of integralization of moral and intellectual education is to know more about diversity then combine with knowledge and practice with morality then achieve the purposes of national education. The conclusions or findings of Freire’s and Ki Hadjar Dewantara’s analysis approach are the absence of differences in the educational portion, the absence of social classes as the limits of education, and the educator has a role as teacher not only as a facilitator but also as a identifierin diversity and be honest about the history, there is a link between learners and educators, mutual understanding, learners receive teaching, and educators learn to understand learners, and this function is summarized in education for freedom and ing ngarsho sung tuladha, ing madyo mangun karsha, tut wur handayani.